Microbial community succession during crude oil-degrading bacterial enrichment cultivation and construction of a degrading consortium - Yu, Tianfei; Liu, Xiaodong; Ai, Jiamin; Wang, Jiamin; Guo, Yidan; Liu, Xinhui; He, Xiaolong; Deng, Zhenshan; Jiang, Yingying (Frontiers in Microbiology, 2022)
Microbial community succession during the enrichment of crude-oil-degrading bacteria was analyzed using Illumina high-throughput sequencing to guide bacterial isolation and construction of a bacterial consortium. Community change occurred in six days; the most abundant phylum changed from Proteobacteria to Actinobacteria; the most abundant genera were Dietzia and unspecified_Idiomarinaceae. Two crude-oil-degrading strains, Rhodococcus sp. OS62-1 and Dietzia sp. OS33, and one weak-crude-oil-degrading strain, Pseudomonas sp. P35, were isolated. A consortium comprising Rhodococcus sp. OS62-1 and Pseudomonas sp. P35 showed the highest crude-oil-degrading efficiency, reaching 85.72 ± 3.21% within seven days, over a wide pH range (5–11) and salinity (0–80 g·l-1). Consumption of saturated hydrocarbons, aromatic hydrocarbons, and resins was greater by the consortium than by a single strain, as was degradation of short-chain-alkanes (C13–C17) according to gas-chromatography. The bacterial consortium provides technical support for bioremediation of crude oil pollution.